A detailed introduction of different beamforming techniques used in 5G. (17th January 2021) - Bindle, Abhay; Gulati, Tarun; Kumar, Neeraj
Summary: The arrival of high‐speed internet facility such as the mmWave system or more commonly known as 5G wireless network is a prime impetus that is expected to be the driver for radical transformation in current communication methods. Apart from the numerous applications, an area where 5G is expected to be a game‐changer is the vehicle‐to‐everything or V2X network. This technology uses a road side unit (RSU) which provides wireless connectivity to vehicles, pedestrians, and so on, which may be either stationary or mobile so that their exact location can be known in real time. Researchers have demonstrated experimentally that 4G connectivity with such RSUs can provide a reliable low latency network for certain applications. For instance, for near‐perfect localization of each connected objects on the map, there is a need to stream GPS data, process semantic information from videos continually using computer vision. While these are simply for locating vehicles in real time so that road accident can be prevented. They are also the host of other features such as entertainment, health monitors, and mobile office that can be integrated inside a moving vehicle. To address the issues massive multi‐input multi‐output (MIMO), communication can be realized by using hybrid transceivers which uses a setup consisting of high‐dimensional analog phase shifters and power amplifier with dimensional digital signal processing units having low power. It is therefore vital to choose an apt beamforming design that will run on low energy. A comparison of different varieties of beamforming methodologies for determining the most efficient massive MIMO network is carried out here. Abstract : A comparison of different varieties of beamforming methodologies for determining the most efficient massive MIMO network for 5G is carried out here. It is observed that the hybrid beamforming technique which is a combined implementation of an analog with a digital beamforming technique aids a massive MIMO wireless communication system in achieving its optimal efficiency.